Legal Policy of State Financial Losses Arrangement In A State-Owned Enterprise - Swardhana, Gde Made; Monteiro, Seguito (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
This research aimed to examine the elements of state loss in regulations concerning the legal policy of state financial arrangements in a bankrupt state-owned enterprise and to analyze the effort of asset recovery related to state loss due to corruption based on the prevailing law in Indonesia and China. This is normative legal research with a comparative approach, with China being taken as a comparison. The study indicated that the elements of state loss are short of money, securities, and goods; it was caused by unlawful actions, either intentionally or negligently; and losses whose amount can be calculated based on the findings of the authorized agency or appointed public accountant, in the Indonesian legal system, asset recovery efforts can be examined from the perspective of criminal law and administrative law. The substance of state finances reveals the same element, namely that the financial loss of SOEs is a loss to state finances. In the execution of court decisions on SOE-owned assets in bankruptcy cases, the regulation does not provide fair legal recognition, protection, certainty, and equal treatment before the law in the management and accountability of state finances.